Study and Design of Adaptively Sealing Machine - Fan Huaxian; Dong Penghao; Dong Wenqi; Hu Shengbang; Jiang Yichao (Jixie chuandong)
In view of the rapid development of logistics industry and the volume of the logistics are gradually increasing,a sealing machine which can automatically seal different boxes is designed. By analyzing the function of sealing machine,including position and sealer. Usually,these functions are separate and uncorrelated,and need different power. In order to contact them,a connecting rod slider mechanism that can contact them is designed. Through the closed vector method,the analysis of the kinematics is finished,the simulation of the motion process is fulfilled by using software MATLAB. The 3 D modeling of the mechanism is carried out by using Solid Works,and the assembly interference is checked. Through the analysis of its motion characteristics and mechanical mechanism,the design parameters of sealing machine are obtained,Using this mechanism,the sealing machine can reduce the number of power,which can simplify the overall structure of sealing machine,reduce manufacturing cost and save energy.